Operation Management Objectives in a Service Operation - Ageev, Aydar (2019)
The goal of this Bachelor Thesis is to explore the changes of the five operational management objectives at the transformation of service operation after the implementation of cloud computing solutions. The documents begin with a description of features in the cloud computing service models. Further, it focuses on operational strategy and the role of five performance objectives in competitive advantage. In the practical part, the thesis represents the framework on how to track changes in five performance objectives after the implementation of technology and analyzing of the company executed by the framework developed in the thesis. As a result of the research, the bachelor thesis evidences the relationships of the five operations performance objectives from a longitudinal perspective. Furthermore, this approach represents a framework to track service operational performance for practitioners.